Influence of Cooling Rate on Cracking and Plastic Deformation during Impact and Indentation of Borosilicate Glasses - Zehnder, Christoffer; Bruns, Sebastian; Peltzer, Jan-Niklas; Durst, Karsten; Korte-Kerzel, Sandra; Möncke, Doris (Frontiers in Materials, 2017)
The influence of a changing glass topology on local mechanical properties was studied in a multi-technique nanomechanical approach. The glass response against sharp contacts can result in structural densification, plastic flow or crack initiation. Using instrumented indentation testing, the mechanical response was studied in different strain rate regimes for a sodium-boro-silicate glass (NBS) exhibiting altering structures due to varying processing conditions. Comparison with data from former studies as well as with literature data on other glass structures helped to elucidate the role of the borate and silicate sub-networks and to understand the overall mechanical properties of the mixed glass systems. A peculiarity of some of the NBS glasses tested in this study is the fact that the connectivity of the borate and silicate entities depends on the sample’s thermal history. While the influence on macroscopic material properties such as E and H is minor, the onset of cracking indeed is influenced by those structural changes within the glass. Rapidly quenched glass shows an improved crack resistance, which is even more pronounced at high strain rates. Studies on various processing conditions further indicate that this transition is closely related to the cooling rate around Tg. The strain rate dependence of cracking is discussed in terms of the occurrence of shear deformation and densification.